The Post-Merger Performance of Acquiring Firms: A Re-Examination of an Anomaly. - Agrawal, Anup; Jaffe, Jeffrey F; Mandelker, Gershon N (Journal of Finance, 1992)
The existing literature on the post-merger performance of acquiring firms is divided. The authors reexamine this issue, using a nearly exhaustive sample of mergers between NYSE acquirers and NYSE/AMEX targets. The authors find that stockholders of acquiring firms suffer a statistically significant loss of about 10 percent over the five-year post- merger period, a result robust to various specifications. Their evidence suggests that neither the firm size effect nor beta estimation problems are the cause of the negative post-merger returns. They examine whether this result is caused by a slow adjustment of the market to the merger event. Their results do not seem consistent with this hypothesis.